Update on yesterday's dose—Use of delivery log-files for daily adaptive proton therapy (DAPT). (23rd September 2020) - Matter, M; Nenoff, L; Marc, L; Weber, D C; Lomax, A J; Albertini, F
Abstract: In daily adaptive proton therapy (DAPT), the treatment plan is re-optimized on a daily basis. It is a straightforward idea to incorporate information from the previous deliveries during the optimization to refine this daily proton delivery. A feedback signal was used to correct for delivery errors and errors from an inaccurate dose calculation used for plan optimization. This feedback signal consisted of a dose distribution calculated with a Monte Carlo algorithm and was based on the spot delivery information from the previous deliveries in the form of log-files. We therefore called the method U pdate On Y esterday's D ose (UYD). The UYD method was first tested with a simulated DAPT treatment and second with dose measurements using an anthropomorphic phantom. For both, the simulations and the measurements, a better agreement between the delivered and the intended dose distribution could be observed using UYD. Gamma pass rates (1%/1 mm) increased from around 75% to above 90%, when applying the closed-loop correction for the simulations, as well as the measurements. For a DAPT treatment, positioning errors or anatomical changes are incorporated during the optimization and therefore are less dominant in the overall dose uncertainty. Hence, the relevance of algorithm or delivery machine errors even increases compared to standard therapy. The closed-loop process described here is a method to correct for these errors, and potentially further improve DAPT.